Attitudes of mathematics teachers towards the use of technological tools in intermediate schools in Saudi Arabia - Alshammari, Yousef (Advances in Social Sciences Research Journal, 2020)
The study aimed to increase understanding of the attitudes of mathematics teachers in intermediate schools towards the use of technological tools in Saudi Arabia in the Hafr Al-Batin province. To achieve the aims of the study, the researchers used a 19-item questionnaire, and its reliability and validity were verified. The sample was 73 male and female mathematics teachers; the study found that the attitudes of mathematics teachers towards the use of technological tools are positive. Finally, the study presented some recommendations: having specialists in the fields of technology and the Internet to help teachers to use technological tools was considered necessary, as well as providing each school with appropriate technological tools, and providing teachers with training courses regarding how to effectively use various technological tools.